2009
DOI: 10.1016/j.abb.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Supercomplexes of the mitochondrial electron transport chain decline in the aging rat heart

Abstract: Accumulation of mitochondrial electron transport chain (ETC) defects is a recognized hallmark of the age-associated decline in cardiac bioenergetics; however, the molecular events involved are only poorly understood. In the present work, we hypothesized that age-related ETC deterioration stemmed partly from disassociation of large solid-state macromolecular assemblies termed "supercomplexes". Mitochondrial proteins from young and old rat hearts were separated by Blue Native-PAGE, protein bands analyzed by LC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
75
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 53 publications
6
75
0
2
Order By: Relevance
“…Alternatively, the present data could also be analyzed in the light of the aging theory and through comparison to a previous report where it was demonstrated that the failing heart in aging results from the loss of respiratory supercomplexes (Gomez et al, 2009). Gómez et al suggested that destabilization of inter-fibrillar mitochondrial string supercomplexes is the responsible for the decline in mitochondrial function during aging (Gomez et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Alternatively, the present data could also be analyzed in the light of the aging theory and through comparison to a previous report where it was demonstrated that the failing heart in aging results from the loss of respiratory supercomplexes (Gomez et al, 2009). Gómez et al suggested that destabilization of inter-fibrillar mitochondrial string supercomplexes is the responsible for the decline in mitochondrial function during aging (Gomez et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Gómez et al suggested that destabilization of inter-fibrillar mitochondrial string supercomplexes is the responsible for the decline in mitochondrial function during aging (Gomez et al, 2009). Moreover, the authors pointed the possible role of Complex IV in the underlying mechanism as it is the only respiratory complex present in all supercomplexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercomplexes have been found in a wide variety of organisms ranging from bacteria and unicellular eukaryotes to multicellular organisms including fungi, higher plants, and mammals (11). In addition, the abundance and/or stability of these supramolecular edifices have been shown to respond to physiological changes (13,14), thus pointing to their physiological relevance. Yet, to our knowledge, functional data supporting these views are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This culminated in the isolation by Acin-Pérez, et al of a functional "respirasome" from mammal cells, transferring electrons all the way from NADH or succinate to molecular oxygen (12). In addition, the composition and abundance of the biochemically characterized supercomplexes have been shown to vary with growth or physiological conditions (13,14), supporting their physiological significance. However, parallel studies on whole cells aimed at understanding the dynamics of the supercomplexes and their functional relevance are lacking.…”
mentioning
confidence: 99%